2007
DOI: 10.1111/j.1365-2486.2007.01496.x
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus inputs unmask negative effects of ultraviolet radiation on algae in a high mountain lake

Abstract: Ultraviolet solar radiation (UVR) and atmospheric nutrient loads to pristine ecosystems are global climate change phenomena that simultaneously affect aquatic organisms in ways not easily predicted by single factor studies. Plankton in a high mountain lake was exposed in situ to increasing phosphorus (P) concentrations (mimicking atmospheric pulses) in absence or presence of UVR in order to identify their interactive effect on functional [primary production, organic carbon (C) release (EOC), and percentage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
95
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(112 citation statements)
references
References 71 publications
12
95
3
1
Order By: Relevance
“…The results presented here indicate increased susceptibility to UVR of bacteria and phytoplankton communities relatively less exposed to UV-B during their life cycles (Pakulski et al, 2007;Harrison and Smith, 2011a). Interestingly, the UVR effect on %EOC was only significant in the high-UVR lake; the release of C has been described as a protective mechanism to prevent photosystem damage from reducing power excess under high irradiance of PAR (Wood and Van Valen, 1990) as well as UVR (Carrillo et al, , 2008. The lack of this "escape valve", which helps to prevent overexcitation of PSII, might be the final cause of the higher sensitivity of phytoplankton communities in the low-UVR lakes.…”
Section: Sensitivity Of Phytoplankton and Bacteria To Uvr And Stratifmentioning
confidence: 84%
See 2 more Smart Citations
“…The results presented here indicate increased susceptibility to UVR of bacteria and phytoplankton communities relatively less exposed to UV-B during their life cycles (Pakulski et al, 2007;Harrison and Smith, 2011a). Interestingly, the UVR effect on %EOC was only significant in the high-UVR lake; the release of C has been described as a protective mechanism to prevent photosystem damage from reducing power excess under high irradiance of PAR (Wood and Van Valen, 1990) as well as UVR (Carrillo et al, , 2008. The lack of this "escape valve", which helps to prevent overexcitation of PSII, might be the final cause of the higher sensitivity of phytoplankton communities in the low-UVR lakes.…”
Section: Sensitivity Of Phytoplankton and Bacteria To Uvr And Stratifmentioning
confidence: 84%
“…La Caldera is a mixed oligotrophic (total phosphorus [TP] < 0.3 µM and chlorophyll a [Chl a] < 5 µg L −1 ) high-mountain lake above the treeline on a siliceous bedrock in a glacial cirque (Carrillo et al, 2006). This lake has a surface area of 2 ha and a mean depth of 4.3 m, with a maximum depth interannually varying from 2 to 14 m. UVR of considerable intensity penetrates deeply in the lake due to the high transparency of the water and low values of dissolved organic carbon ([DOC] < 0.08 mM) as reported in Carrillo et al (2008) and Helbling et al (2013). Therefore, this lake is hereafter called the "high-UVR" lake.…”
Section: Model Ecosystemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Medina-Sánchez et al (2002) also reported that UVB radiation inhibited bacteria when they were strongly P-deficient, whereas UVB exerted no direct effect on bacterial activity when they were not P-limited. A recent study showed that phosphorus amendment and UVR exposure had a synergistic negative effect on phytoplankton (Carrillo et al 2008).…”
Section: Factors Regulating Uvr Effectsmentioning
confidence: 99%
“…For example, nutrient stress may weaken or mask the UVB stress (Xenopoulos et al 2002), while a nutrient amendment (e.g. P addition) had a negative effect on phytoplankton subjected to UVR exposure (Carrillo et al 2008). …”
Section: Implications For Uv Effects On Trophic Levelsmentioning
confidence: 99%